2019
DOI: 10.1007/s43441-019-00023-3
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Advanced Technologies to Augment Pharmacovigilance Systems: Challenges and Opportunities

Abstract: There are significant challenges and opportunities in deploying and utilizing advanced information technology (IT) within pharmacovigilance (PV) systems and across the pharmaceutical industry. Various aspects of PV will benefit from automation (e.g., by improving standardization or increasing data quality). Several themes are developed, highlighting the challenges faced, exploring solutions, and assessing the potential for further research. Automation of the workflow for processing of individual case safety re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 27 publications
0
25
0
4
Order By: Relevance
“…Further analysis is needed to evaluate which technologies are best suited for which ICSR process steps and how such solutions can be validated and sustained over the long term. Similar research needs to be performed for signal detection, aggregate safety reporting, risk management, and other pharmacovigilance processes to extend the benefit of intelligent automation beyond the ICSR process [18].…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis is needed to evaluate which technologies are best suited for which ICSR process steps and how such solutions can be validated and sustained over the long term. Similar research needs to be performed for signal detection, aggregate safety reporting, risk management, and other pharmacovigilance processes to extend the benefit of intelligent automation beyond the ICSR process [18].…”
Section: Discussionmentioning
confidence: 99%
“…Processing of an AE is an expensive resource-intensive process, which includes a high risk of errors and operational inefficiencies (Ghosh et al, 2020). A detailed review of the literature concluded that innovative technology such as data mining, machine learning, AI, and robotics could result in new operating models for PV (Beninger & Ibara, 2016;Lai, 2017), improve efficiencies and reduce PV operations costs (Karimi et al, 2015;Lu, www.jpadr.com m 2009;Schmider et al, 2018), better allocation of resources, and improve patient outcomes (Lewis & McCallum, 2019). In this doctoral study, we explored the strategies that PV systems managers in the pharmaceutical industry use to implement innovative technology solutions to automate AEs case processing (see System's model in Fig 2) The single case that we selected to study was the implementation of an innovative technology solution to automate AE processing.…”
Section: Applications To Professional Practicementioning
confidence: 99%
“…This will save the time, cost, and manpower required for these activities. Introducing AI in PV also improves the quality and accuracy of drug safety results [12,13].…”
Section: Utilization In Case Processingmentioning
confidence: 99%